UNIVERSITAS BRAWIJAYA STUDENT CONDITION DEPICTED IN AGUSTANTO SUPRAYOGI PETITION POSTED ON CHANGE.ORG - Rahmad Novianto Ardiansyah (Universitas Muhammadiyah Surakarta, 2019)
This study aims to find how the writer of petition represent Universitas Brawijaya student condition on 2016 through word choice, and also to find the ideology behind the petition “Ganti WR III Unibraw Malang u/ Selamatkan Mahasiswa IKA Unibraw Malang dari Perpecahan”. The author used 3 stages of Fairclough Critical Discourse Analysis (CDA) framework in this study, text analysis, discourse practice, and social practice. The result of this study is there were 16 data that represent how the student were oppressed (3 data) and the Vice-Rector III abusive act (13 data). The ideology behind this petition itself is how students experience persecution by WR 3 illustrated by the selection of words described by the petitioners. The ideology does not escape the author's social background, social conditions, and norms that apply to student life in UB at that time.